Heart valve calcification in patients with coronary heart disease - S. A. Dovgolis; I. Yu. Kucherova; E. A. Kozlov; I. G. Fomina (Кардиоваскулярная терапия и профилактика)
Aim. To study mitral and aortic valve calcification prevalence in patients with coronary heart disease (CHD), and its influence on myocardial status. Material and methods. Echocardiography was performed in 214 CHD patients (119 females, 95 males; mean age 59.0±8.3 years). Mitral and aortic valve calcification, regurgitation, ejection fraction, diastolic dysfunction, left cardiac chamber sizes, and atherosclerosis risk factors were studied. Results. Calcification of aortial and mitral valves was found in 74 (34.5%) patients with CHD. All of them were above 40, 46% - older than 70; 50 (68%) patients were females. Combination of CHD and arterial hypertension (AH) was observed in 26 (35%) patients. Aortic or mitral valve calcification was found in 86% and 53% of the cases, respectively. Regurgitation was observed in 17 (23%) participants, left atrial dilatation and diastolic dysfunction – in 89%, left ventricular hypertrophy – in 74%. Conclusions: Aortic and mitral valve calcification was observed in 74 (35.5%) participants with CHD. Most of these patients were above 60 years, females, suffering from AH and diabetes mellitus. Aortic valve was affected in 86% of the cases; frequency of mitral calcification increased with age. The prevalence of left atrial dilatation, left ventricular hypertrophy and diastolic dysfunction was higher by 8%, 19%, and 13%, respectively, than that in individuals with intact valves. Ejection fraction did not differ in both groups.